On the convergence of sigmoidal fuzzy grey cognitive maps - Harmati, István Á.; Kóczy, László T. (Zielona Góra: Uniwersytet Zielonogórski)
Fuzzy cognitive maps (FCMs) are recurrent neural networks applied for modelling complex systems using weighted causal relations. In FCM-based decision-making, the inference about the modelled system is provided by the behaviour of an iteration. Fuzzy grey cognitive maps (FGCMs) are extensions of fuzzy cognitive maps, applying uncertain weights between the concepts.
Keywords: fuzzy cognitive maps; grey system theory; fuzzy grey cognitive map; fixed point